Modelos de equilibrio general y análisis de políticas - Alliance of Bioversity International and CIAT (Bioversity International and the International Center for Tropical Agriculture, 2024)
This playlist is a collection of video from the Modelos de equilibrio general y análisis de políticas Workshop, last 12 & 14 March 2024. This workshop is a joint effort of the Alliance of Bioversity and CIAT, in partnership with the International Food Policy Research Institute (IFPRI), has been instrumental in promoting and strengthening the integration of policy and investment tools in Colombia through the CGIAR Research Initiative on National Policies and Strategies (NPS).